PENGARUH GAYA KEPEMIPINAN, BUDAYA ORGANISASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN (Studi Kausal di Layanan Social Media TelkomCare Telkom Indonesia Jakarta) - Ardhiyaningtyas, Ria Cendana; Faisal, Ahmad (JURNAL ILMIAH M-PROGRESS, 2019)
This study aims to obtain empirical data, facts, and valid and correct information, and can be trusted, about Leadership Style, Organizational Culture and Work Stress on Employee Performance. Using a quantitative research approach and the survey method. To prove the influence of the variables of Leadership Style, Organizational Culture and Job Stress on Performance in this study, data analysis techniques were carried out with Path Analysis. Based on the results of the research analysis:There is a positive and significant direct effect of the Leadership Style variable on Job Stress. There is a positive and significant direct effect of the Organizational Culture variable on Job Stress. There is a positive and significant direct effect of the Leadership Style variable on Performance. There is a positive and significant direct effect of the Organizational Culture variable on the Performance variable. There is a positive and significant direct effect of the Job Stress variable on the Performance variable.Â Keywords: Leadership Style, Organizational Culture, Job Stress and PerformanceÂ